«The ghosts are themselves the future»: L’eredità queer di Chiara Fumai - Pipicelli, Irene (Mimesis Journal, 2021)
The paper aims to broaden the critical account of Chiara Fumai’s work in thematic and methodological terms, integrating the queer perspective as critical insight into the artist’s work. This addition enables a more exhaustive framework of analysis by bringing to light a dense thematic complexity, otherwise unexplored. Furthermore, it presents the advantage of not competing with the critical paths opened until now, rather resonating with them. The first part of the paper is de-voted to an overview of Fumai’s artistic biography through a works’ selection analysis. This overview is preparatory to the critical proposal emerging in the second part, where the author considers the feminist critical lecture of the artist’s work and propose to flank it with conceptual tools derived from queer theory.